Growth pattern and condition factor of yellowfin tuna Thunnus albacares (Bonnaterre, 1788) in Eastern Indian Ocean - Suciadi Catur Nugroho; Irwan Jatmiko; Arief Wujdi (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2018)
Yellowfin tuna, Thunnus albacares (Bonnaterre, 1788) is one of the important economically for tuna species that spread in Indonesian waters, including in WPP 572 (Indian Ocean west coast of Sumatra). One important aspect relating to sustainable utilization is the growth pattern and the condition factor. This study aims to examine growth patterns and factor conditions of yellowfin tuna in the Eastern Indian Ocean. The number of fish samples measured in length and weight is 7,550 with length range from 76-176 cm (average: 129.03 cm) and mode at 150 cm. The length weight relationship of the species is W=4x10-5L2.842 (R2 0,957). In general the growth pattern of yellowfin tuna is negative allometric which means that the length increase is faster than the weight. The average relative condition factor of yellowfin tuna is 0.975 with a tendency to decrease along with the increasing of its length. The highest relative condition factor occurred at the length class of 80 cm with 1,061 and the lowest occurred at length 170 cm with 0.918. The monthly relative condition factor generally increased twice in one year from February to June and from July to December. Abstrak Tuna madidihang, Thunnus albacares (Bonnaterre,1788), merupakan salah satu spesies tuna ekonomis penting dan ter-sebar di perairan Indonesia, termasuk di WPP 572 (Samudra Hindia bagian barat Sumatera). Salah satu aspek penting yang berkaitan dengan upaya pemanfaatan berkelanjutan adalah pola pertumbuhan dan faktor kondisi. Penelitian ini bertujuan untuk mengkaji pola pertumbuhan dan faktor kondisi ikan madidihang di Samudra Hindia Bagian Timur. Jumlah ikan contoh yang diukur panjang dan bobotnya adalah 7.550 ekor yang mempunyai sebaran panjang 76-176 cm (rata-rata 129,03 cm) dan modus 150 cm. Hubungan panjang bobot ikan tersebut adalah W = 4x10-5L2,842 (R2 0,957). Secara umum pola pertumbuhan madidihang bersifat allometrik negatif yang berarti bahwa pertambahan panjang lebih cepat daripada bobotnya. Faktor kondisi relatif rata-rata madidihang adalah 0,975 dengan kecenderungan menurun seiring bertambahnya ukuran panjang. Faktor kondisi relatif tertinggi terjadi pada kelas panjang 80 cm sebesar 1,061 dan terendah terjadi pada kelas panjang 170 cm sebesar 0,918. Faktor kondisi relatif bulanan secara umum mengalami dua kali peningkatan dalam satu tahun yaitu dari bulan Februari hingga Juni dan dari Bulan Juli hingga Desember.